Oxidative stress, NO [rad] and smooth muscle cell extracellular superoxide dismutase expression - Strålin, Pontus; Jacobsson, Håkan; Marklund, Stefan L (Biochimica et biophysica acta, 2003)
Oxygen free radicals apparently play important roles in diseases of the blood vessel wall and increased secretion of superoxide radicals occurs in many situations. The vascular wall contains large amounts of extracellular superoxide dismutase (EC-SOD). The synthesis of the enzyme by the smooth muscle cells (SMC) is modulated by cytokines, growth factors, and vasoactive factors. Here we studied the effects of oxidants (pyrogallol, xanthine oxidase, Cu and Fe), antioxidants (SOD, catalase, and ascorbate), glutathione modulation ( n-acetylcysteine and buthionine sulfoximine) and nitric oxide on EC-SOD expression by human vascular SMCs. Generally, the responses in EC-SOD synthesis were small, and no changes were noted in mRNA levels. High concentrations of some of the agents caused reductions in EC-SOD synthesis, mostly concomitantly with toxic effects on the cells. Cell cultures are normally ascorbate deficient, and addition of ascorbate to approach physiological levels doubled the EC-SOD content. Iron ions up-regulated EC-SOD synthesis but also blocked the secretion of the enzyme. Only down-regulation was found by NO -releasing compounds. In conclusion, there is limited response to oxidant stress of EC-SOD synthesis by SMCs on a cell-autonomous level. The synthesis appears mainly regulated by factors coordinating concerted tissue responses.